Big Five aspects of personality interact to predict depression. Issue 4 (20th October 2017) - Allen, Timothy A.; Carey, Bridget E.; McBride, Carolina; Bagby, R. Michael; DeYoung, Colin G.; Quilty, Lena C.
Abstract: Objective: Research has shown that three personality traits—Neuroticism, Extraversion, and Conscientiousness—moderate one another in a three‐way interaction that predicts depressive symptoms in healthy populations. We test the hypothesis that this effect is driven by three lower‐order traits: withdrawal, industriousness, and enthusiasm. We then replicate this interaction within a clinical population for the first time. Method: Sample 1 included 376 healthy adults. Sample 2 included 354 patients diagnosed with current major depressive disorder. Personality and depressive tendencies were assessed via the Big Five Aspect Scales and Personality Inventory for DSM‐5 in Sample 1, respectively, and by the NEO‐PI‐R and Beck Depression Inventory‐II in Sample 2. Results: Withdrawal, industriousness, and enthusiasm interacted to predict depressive tendencies in both samples. The pattern of the interaction supported a "best two out of three" principle, in which low risk scores on two trait dimensions protects against a high risk score on the third trait. Evidence was also present for a " worst two out of three" principle, in which high risk scores on two traits are associated with equivalent depressive severity as high risk scores on all three traits. Conclusions: These results highlight the importance of examining interactive effects of personality traits on psychopathology.